Hubungan Pengetahuan Ibu Tentang Pemenuhan Gizi Seimbang Dengan Status Gizi Pada Balita Usia 24-35 Bulan Di Desa Manjung Ngawen, Klaten - Sri Wahyuni; Astri Wahyuningsih; Lilik Hartati (Stikes Muhammadiyah Klaten, 2022)
Nutrition is an important factor that aims to build quality human resources. The impact of malnutrition is low body resistance so that the body is susceptible to infectious diseases, lack of energy and protein which causes impaired growth and development of toddlers. Mother's knowledge about balanced nutrition is very important, considering the role of mothers in the family as food managers. The purpose of this study was to determine the mother's knowledge about the fulfillment of balanced nutrition with nutritional status in toddlers. The research design used is descriptive correlation with a cross sectional approach. The research sample amounted to 38 respondents using the Total Sampling technique. data collection using questionnaires and observation sheets, data were analyzed using the Kendall Tau test with a significant level of 0.05. The results showed that most of the mother's knowledge about the fulfillment of balanced nutrition was sufficient, namely a number of 22 respondents (57.9%) for the nutritional status of toddlers, most of them were good, namely 31 respondents (81.6%), sufficient knowledge with good nutritional status of toddlers as much as 20 respondents (52.6%). The conclusion in this study is that there is a relationship between mother's knowledge about the fulfillment of balanced nutrition with nutritional status in toddlers aged 24-35 months with a p value of 0.020 (p>0.05). It is hoped that in collaboration with posyandu cadres to continue to routinely provide counseling about balanced nutrition for toddlers to mothers in Manjung Village